Peran Badan Kesatuan Bangsa Dan Politik Kabupaten Sidoarjo dalam Penerimaan, Pembinaan, dan Pengawasan Organisasi Masyarakat - Elviora, Meylisa; Prathama, Ananta (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the role of the National Unity and Political Agency in receiving reports on the existence of community organizations in Sidoarjo Regency, as well as the challenges faced in carrying out this task. (mass organizations) in Sidoarjo Regency, as well as the challenges faced in carrying out this task. The method method used is Qualitative through observation. The result of the research The results showed that the National Unity and Political Agency plays an important role in the the guidance and supervision of mass organizations, ensuring that registered mass organizations fulfill the applicable legal requirements. applicable legal requirements. However, there are still challenges such as radicalization, lack of resources, and negative stigma towards certain CSOs. certain mass organizations. This research recommends increasing the capacity of human resources in the National Unity and Political Unity Agency, socializing more effective regulations, and strengthening the stigma against certain mass organizations. Political Unity Agency, more effective socialization of regulations, as well as strengthening cooperation with other institutions to increase the effectiveness of with other institutions to improve the effectiveness of management.